Study of fiscal decentralization, macroeconomic stability and regional growth in Indonesia - Joko Tri Haryanto; Rita Helbra Tenrini (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2021)
Indonesia has been implementing fiscal decentralization since 2001. In theory, fiscal decentralization affected macroeconomic stability and economic growth—this study using data panels at the provincial level from 2010 to 2013. In the relationship between fiscal decentralization and macroeconomic stability with control variable income, significant variables are income to GRDP, GRDP per capita, and population. If control variable expenditure, significant variables are expenditure to GRDP, GRDP per capita, and population. In the model that analyzes fiscal decentralization and economic growth with control variable income, significant variables are income to GRDP, consumption to GRDP, and population. Meanwhile, if control variable expenditure, significant variables are expenditure to GRDP, consumption to GRDP, and population. By using sensitivity analysis, the population variable is a high priority. Therefore stakeholders should treat population variables carefully.